Power control and rate management for wireless multimedia CDMA systems. - Chi Wan Sung (IEEE Transactions on communications)
We consider a wireless multimedia code-division multiple-access system, in which the terminals transmit at different rates. We formulate the problem as a constrained optimization problem, with the objective of maximizing the total effective rate. An optimal power control strategy is derived. When the scale of the system is large, the optimal solution takes a simple form, which is easy to be applied practically. Furthermore, our basic model can be extended to include delay-sensitive traffic